Prototipe GOT TOTEMUSINNING (Great Sorting Metal Monitoring System Using Internet of Things) - Muslim, Andi Muhamad; Fahmy, Muhamad; Syufrijal (LPPM Universitas Negeri Jakarta, 2020)
The final project aims to make a prototype GOT TOTEMUSINNING (Great Sorting Metal Monitoring System Using Internet of Things). The research method uses the method of making prototyping. Making prototypes begins with gathering needs, building prototyping, evaluating prototyping, coding the system, testing the system and evaluating the system. The Metal Proxymity sensor to detect metal waste, Inductive Proxymity to detect non-metallic waste, Ultrasonic Sensor to detect whether the waste is fully charged, Module DF-Player as a module that can process metal waste, Inductive Proxymity to detect non-metallic waste, Ultrasonic Sensor to detect whether the waste is fully charged, Module DF-Player as a module that can process sound / MP3 and WEMOS D1 as the process. There are speakers as outputs that are used to inform the type of waste and the UBIDOTS website provides information on garbage being fully loaded. Based on the results test, the prototype have done has been successfully made and has been tested can detect metal and non-metal waste. When the prototype is fully loaded it can also send information to UBIDOTS. Penelitian ini bertujuan membuat Prototipe GOT TOTEMUSINNING (Great Sorting Metal Monitoring System Using Internet Of Things). Metode penelitian menggunakan metode pembuatan prototyping. Pembuatan prototipe di awali dengan melakukan pengumpulan kebutuhan, membangun prototyping, evaluasi prototyping, mengkodekan sistem, menguji sistem dan mengevaluasi sistem. Sensor Metal Proxymity untuk mendeteksi sampah logam, Inductive Proxymity untuk mendeteksi sampah nonlogam, Sensor Ultrasonic untuk mendeteksi apakah sampahnya sudah terisi penuh, Module DF- Player untuk sebagai module yang dapat memproses suara/MP3 dan WEMOS D1 sebagai prosesnya. Terdapat speaker sebagai output yang digunakan untuk memberitahu jenis sampah dan web UBIDOTS memberikan informasi sampah sudah terisi penuh. Berdasarkan hasil pengujian, prototipe sudah berhasil dibuat dan sudah diuji dapat mendeteksi sampah logam dan nonlogam. Ketika prototipe terisi penuh juga dapat mengirimkan informasi ke UBIDOTS